Biological Activities and Chemical Composition of Methanolic Extracts of Selected Autochthonous Microalgae Strains from the Red Sea - Pereira, Hugo (Mar Drugs, 2015)
Four lipid-rich microalgal species from the Red Sea belonging to three different genera (Nannochloris, Picochlorum and Desmochloris), previously isolated as novel biodiesel feedstocks, were bioprospected for high-value, bioactive molecules. Methanol extracts were thus prepared from freeze-dried biomass and screened for different biological activities. Nannochloris sp. SBL1 and Desmochloris sp. SBL3 had the highest radical scavenging activity against 1,1-diphenyl-2-picrylhydrazyl, and the best copper and iron chelating activities. All species had potent butyrylcholinesterase inhibitory activity (>50%) and mildly inhibited tyrosinase. Picochlorum sp. SBL2 and Nannochloris sp. SBL4 extracts significantly reduced the viability of tumoral (HepG2 and HeLa) cells with lower toxicity against the non-tumoral murine stromal (S17) cells. Nannochloris sp. SBL1 significantly reduced the viability of Leishmania infantum down to 62% (250 µg/mL). Picochlorum sp. SBL2 had the highest total phenolic content, the major phenolic compounds identified being salicylic, coumaric and gallic acids. Neoxanthin, violaxanthin, zeaxanthin, lutein and β-carotene were identified in the extracts of all strains, while canthaxanthin was only identified in Picochlorum sp. SBL2. Taken together, these results strongly suggest that the microalgae included in this work could be used as sources of added-value products that could be used to upgrade the final biomass value.